1975
DOI: 10.1152/jappl.1975.38.6.1083
|View full text |Cite
|
Sign up to set email alerts
|

Strength of pulmonary vascular response to regional alveolar hypoxia

Abstract: Regional alveolar hypoxia in the lung induces regional pulmonary vasoconstriction which diverts blood flow from the hypoxic area. However, the predominant determinant of the distribution of perfusion in the normal erect lung is gravity so that more perfusion occurs at the base than at the apex. To determine the strength of the regional alveolar hypoxic response in diverting flow with or against the gravity gradient a divided tracheal cannula was placed in anesthetized dogs and unilateral alveolar hypoxia creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It is interesting to note that oxygen want and carbon dioxide ... call forth a contraction of the lung vessels, thereby increasing the blood flow to better aerated lung areas, which leads to improved conditions for the utilization of alveolar air." Consistent with this proposal, numerous reports subsequently demonstrated that ventilating a sublobar lung region (653,1012), lung lobe (103,141,143,422,1192,1645,1761,1764,1852), or an individual lung (355,380,415,421,473,717,719,778,1192,1435,1579,1823,1825,1999) with an hypoxic gas mixture (F I O 2 ϭ 0 -13%) while ventilating the remaining lung with a normoxic or hyperoxic gas mixture decreased blood flow in the hypoxic region by 20 -100%. Since total flow was unaltered, these decreases represent diversion of flow from hypoxic to nonhypoxic lung due to HPV in hypoxic lung.…”
Section: Overviewmentioning
confidence: 74%
“…It is interesting to note that oxygen want and carbon dioxide ... call forth a contraction of the lung vessels, thereby increasing the blood flow to better aerated lung areas, which leads to improved conditions for the utilization of alveolar air." Consistent with this proposal, numerous reports subsequently demonstrated that ventilating a sublobar lung region (653,1012), lung lobe (103,141,143,422,1192,1645,1761,1764,1852), or an individual lung (355,380,415,421,473,717,719,778,1192,1435,1579,1823,1825,1999) with an hypoxic gas mixture (F I O 2 ϭ 0 -13%) while ventilating the remaining lung with a normoxic or hyperoxic gas mixture decreased blood flow in the hypoxic region by 20 -100%. Since total flow was unaltered, these decreases represent diversion of flow from hypoxic to nonhypoxic lung due to HPV in hypoxic lung.…”
Section: Overviewmentioning
confidence: 74%
“…During venous gas infusion, however, hyperoxia impairs CO2 elimination as seen from the increased values of Рзк,_ and (a-A)D(->Q as compared with normoxia (Table 2), which are indicative of an increased alveolar and therefore physiological dead space. It is generally accepted that oxygen plays a major role in the regulation of the ventilation-perfusion ratio of lung units (Duke and Lee, 1963;Fishman, 1961;Hales et al, 1975;Severinghaus et al, 1961;West, 1969). During pulmonary embolism there already is a shift of blood flow to lung units with low ventilation-perfusion ratios as described above.…”
Section: Discussici!mentioning
confidence: 94%
“…During venous gas infusion, however, hyperoxia impairs CO2 elimination as seen from the increased values of Рзк,_ and (a-A)D(->Q as compared with normoxia (Table 2), which are indicative of an increased alveolar and therefore physiological dead space. It is generally accepted that oxygen plays a major role in the regulation of the ventilation-perfusion ratio of lung units (Duke and Lee, 1963;Fishman, 1961;Hales et al, 1975;Severinghaus et al, 1961;West, 1969). During pulmonary embolism there already is a shift of blood flow to lung units with low ventilation-perfusion ratios as described above.…”
Section: Discussici!mentioning
confidence: 94%